Reducing Blood Testing in Pediatric Patients after Heart Surgery: Proving Sustainability - Bodily, Stephanie A. (Pediatr Qual Saf, 2017)
INTRODUCTION: Frequent blood testing increases risk of iatrogenic anemia, infection, and blood transfusion. This study describes 3 years of sustained blood testing reduction from a quality improvement (QI) initiative which began in 2011. METHODS: The cohort consisted of postop children whose surgery had a Risk Adjustment for Congenital Heart Surgery (RACHS) classification consecutively admitted to a tertiary Cardiac Intensive Care Unit. Data were collected for a 2010 preintervention, 2011 intervention, and 2012–13 postintervention periods, tabulating common laboratory studies per patient (labs/pt) and adjusted for length of stay (labs/pt/d). The QI initiative eliminated standing laboratory orders and changed to testing based on individualized patient condition. Adverse outcomes data were collected including reintubation, central line–associated bloodstream infections and hospital mortality. Safety was measured by the number of abnormal laboratory studies, electrolyte replacements, code blue events, and arrhythmias. RESULTS: A total of 1169 patients were enrolled (303 preintervention, 315 intervention, and 551 postintervention periods). The number of labs/pt after the QI intervention was sustained (38 vs. 23 vs. 23) and labs/pt/d (15 vs. 11 vs. 10). The postintervention group had greater surgical complexity (P = 0.002), were significantly younger (P = 0.002) and smaller (P = 0.008). Children with RACHS 3–4 classification in the postintervention phase had significant increased risk of reintubation and arrhythmias. CONCLUSIONS: After the implementation of a QI initiative, blood testing was reduced and sustained in young, complex children after heart surgery. This may or may not have contributed to greater reintubation and arrhythmias among patients with RACHS 3–4 category procedures.